THE INFLUENCE OF CR, DQ, ROI, INVENTORY TURNOVER ON STOCK MARKET PRICE IN PLANTATION COMPANIES, SUB-SECTOR OF PALM OIL - Albert Ronaldo Hutasoit; Listari Laia; Ronald Hasudungan; Septony B Siahaan (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
The point of this inquire about is to get it the relationship between Current Proportion, Obligation to Value Proportion, Return on Speculation, and Stock Trunover on Stock Advertise Costs in manor companies recorded on the IDX for the period 2018 – 2020. A quantitative inquire about strategy with a clear approach was utilized in this ponder, with a populace of 13 companies decided through purposive testing procedure. Based on the comes about of the consider, it appears that somewhat Return on Venture and Stock Turnover have a positive and noteworthy impact on the Stock Advertise Cost of oil palm ranch companies recorded on the IDX. In expansion, the Obligation to Value Proportion in part includes a positive but immaterial impact on the Stock Advertise Cost of oil palm manor companies recorded on the IDX. In the interim, the Current Proportion mostly features a negative and immaterial impact on the Stock Showcase Cost of oil palm manor companies recorded on the IDX. Synchronous comes about appear that the Current Proportion, Obligation to Value Proportion, Return on Venture, and Stock Trunover have a positive and immaterial impact on the Stock Advertise Cost of palm oil companies recorded on the IDX